Aspectos emocionais de procedimentos de ensino de professores de ciências do ensino médio - Jordelina Lage Martins Wykrota (2007)
The number of studies on emotions is growing in the last years, in the educational and Science Teaching research, although yet rare. This research sought evidences of the occurrence and relevance of high school teachers emotions during their science teaching procedures. First, we present a theoretical frame based in recent theories about mind, consciousness and cognition in order to integrate such concepts and to approach one vis-à-vis the other ones. Then, we depart from a developmental-interacionist theory for the triad motivation-emotion-cognition, proposed by BUCK (1999) to establish three levels and means of emotions manifestation: physiological variations, expression and subjective experience. Therefore, we designed this research to catch psychological, socio-cultural and biological aspects of teachers emotions on their teaching routines. Five teachers were chosen after voluntary and explained consent and participated in this study. We have studied each teachers context by technical visits to their school work place, interviews with their supervisors and peers, and informal following up during at least one year. Data gathering refers to episodes of planning, execution and evaluation of at least one class (50 minutes) for each teacher. We used open interview and the explicitation interview techniques (entretien dexplicitation, VERMERSCH, 2003) to attain descriptions of subjective experiences; register in video and observation of teacher procedures to obtain the emotional expressions; and register of heart rate frequency to realize the physiological changes possibly related to emotional processes. We present the results in two sections: in the first part, one case study for each of the five teachers, who validated the text of her/his case. In the second part, we present the analysis of heart rate variability of one of the teachers. We compared such analysis with the analysis of two other emotional manifestations: the expression and subjective experience. 7 Based on the analysis of each case study and on this second study, we show the diversity and relevance of the emotions of high school science teachers; the relation between teachers emotions and motivation; their regulation of such emotions and; the socio-cultural influence in these emotions; the influence of emotions in their decision-making in the course of their pedagogical actions; the relevance and importance of teachers sincretic cognition about their emotional states. Emotional states can be regulated, represented and masked, but they determine the bulk of teachers decision-making in the course of planning, performing and evaluating the instruction. Teachers education about their emotional states needs mediation, as the person that manifests an emotional state does not necessarily consciously perceive it. An important implication of the results of this work is that the teachers embodied knowledge learned by the teaching traditions and practice has an enormous weight in teachers decision-making. As a component of teachers talent to create innovative solutions to problematic situations, it cannot be neglected. Moreover, it needs more and better scrutiny.